2017
DOI: 10.3389/fimmu.2017.01274
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines and Chemokine Receptors: Accomplices for Human Immunodeficiency Virus Infection and Latency

Abstract: Chemokines are small chemotactic cytokines that are involved in the regulation of immune cell migration. Multiple functional properties of chemokines, such as pro-inflammation, immune regulation, and promotion of cell growth, angiogenesis, and apoptosis, have been identified in many pathological and physiological contexts. Human immunodeficiency virus (HIV) infection is characterized by persistent inflammation and immune activation during both acute and chronic phases, and the “cytokine storm” is one of the ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 148 publications
1
22
0
Order By: Relevance
“…Several other studies have shown that, in addition to TNF-α and IL-10, HIV-1 enveloped glycoproteins also stimulate the production of a variety of pro-inflammatory and anti-inflammatory cytokines/chemokines, including IL-1β, IL-6, IL-8, IL-18, IL-23, IL-27, CCL2, CCL4, CCL20, CXCL2, CXCL13, and TSLP 62 64 that are also implicated in HIV-1 associated impairment of the immune system 52 , 53 , 63 , AIDS-related diseases, and the aberrant sustained hyper immune-activation 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…Several other studies have shown that, in addition to TNF-α and IL-10, HIV-1 enveloped glycoproteins also stimulate the production of a variety of pro-inflammatory and anti-inflammatory cytokines/chemokines, including IL-1β, IL-6, IL-8, IL-18, IL-23, IL-27, CCL2, CCL4, CCL20, CXCL2, CXCL13, and TSLP 62 64 that are also implicated in HIV-1 associated impairment of the immune system 52 , 53 , 63 , AIDS-related diseases, and the aberrant sustained hyper immune-activation 65 , 66 .…”
Section: Discussionmentioning
confidence: 99%
“…SDF-1/CXCL12 is the most primitive chemokine that regulates development in multiple systems and diverse cell functions, including proliferation and survival in the immune system, through the two known receptors CXCR4 and ACKR3. [13,15,20] Interestingly, the affinity of CXCL12/SDF-1 for CXCR4 correlates well with its action as a suppressor of infection by T-tropic HIV-1 species and its ability to induce CXCR4 internalization. [21] In this context, the observed adverse effect of SDF-1 gene expression on the natural history of HIV-1 disease could be explained by the fact that the SDF-1À3 0 T allele was more likely to be associated with detectable X4-tropic viruses.…”
Section: Discussionmentioning
confidence: 99%
“…In HIV‐1 infection, chemokine receptors are used as co‐receptor for viral entry, the virus hijacks the cytoskeleton machinery to favor integration in the host genome, and can alter chemokine production. Wang and colleagues have recently published a comprehensive review, on the role of chemokines and chemokine receptors in the pathogenesis of HIV‐1 infection . In this chapter, we discuss how alterations, induced by chronic immune activation associated to the viral infection, can blunt the responses of T cells to chemokines.…”
Section: Modulation Of Chemokine Activity During Hiv‐1 Infectionmentioning
confidence: 99%